(untitled) (The Journal of Building and Land Development, 2018)
The Planning Programme at the University of the Witwatersrand is the oldest in South Africa. Located in Gauteng, South Africa‟s economic heartland, the two professional planning programmes - a BSc and B.Sc. Hons (Urban and Regional Planning) and a MSc (Development Planning), aim to produce graduates who understand and are able to respond to the contextual challenges of a complex, dynamic and rapidly growing city region. An assessment of the programmes by staff and past students suggests that curricula are generally appropriate, but some areas such as environment, transport, and certain technical aspects of planning could be strengthened.